Colorectal cancer targeted Irinotecan-Assam Bora rice starch based microspheres: a mechanistic, pharmacokinetic and biochemical investigation. (December 2013) - Ahmad, Mohammad Zaki; Akhter, Sohail; Anwar, Mohammed; Kumar, Atul; Rahman, Mahfoozur; Talasaz, Azita Hajhossein; Ahmad, Farhan Jalees
Abstract : The purpose of this investigation was to evaluate the colon-targeted Irinotecan Hydrochloride (ITC-HCl) loaded microspheres by pharmacokinetic and biochemical studies. The microspheres were prepared by double emulsion solvent evaporation method with natural polymer Assam Bora rice starch. The microspheres were characterized for their micromeritics properties, incorporation efficiency, in vitro and in vivo drug release studies. The release study confirmed the insignificant release of ITC-HCl in physiological condition of stomach and small intestine and major drug release in the caecal content. In vivo release study of the optimized microsphere was compared with immediate release (IR) ITC-HCl. ITC-HCl was distributed predominantly in the upper GI tract from the IR, whereas ITC-HCl was distributed primarily to the lower part of GI tract from the microspheres formulation. Enhanced levels of liver enzymes were found in animals given IR ITC-HCl as well as augmented levels of serum albumin, creatinine, leucocytopenia and thrombocytopenia was also observed. In summary, Assam Bora rice starch microspheres exhibit slow and extended release of ITC-HCl over longer periods of time with reduced systemic side-effects.